Abiotic Stress Signaling in Wheat – An Inclusive Overview of Hormonal Interactions During Abiotic Stress Responses in Wheat - Abhinandan, Kumar; Skori, Logan; Stanic, Matija; Hickerson, Neil M. N.; Jamshed, Muhammad; Samuel, Marcus A. (Frontiers in Plant Science, 2018)
Rapid global warming directly impacts agricultural productivity and poses a major challenge to the present-day agriculture. Recent climate change models predict severe losses in crop production worldwide due to the changing environment and in wheat this can be as large as 42 Mt / °C rise in the temperature. Although wheat occupies the largest total harvested area (38.8%) among the cereals including rice and maize, its total productivity remains the lowest. The major production losses in wheat are caused more by abiotic stresses such as drought, salinity and high temperature than the biotic insults. Thus, understanding the effects of these stresses become indispensable for wheat improvement programs which have largely depended on the genetic variations present in wheat genome through conventional breeding. Notably, recent biotechnological breakthroughs in the understanding of gene functions and access to the whole genome sequences have opened new avenues for crop improvement. Despite the availability of such resources in wheat, progress is still limited to the understanding of the stress signaling mechanisms using model plants such as Arabidopsis, rice (monocot) and Brachypodium (as a model plant for wheat) and not directly using wheat as the model organism. This review presents an inclusive overview of the phenotypical and physiological changes due to various abiotic stresses followed by the current state of knowledge on the identified mechanisms of perception and signal transduction in wheat. Specifically, this review presents an exclusive overview of different hormonal regulations observed during abiotic stress signaling in wheat.